Influence of functionalized molybdenum disulfide (MoS2) with triazine derivatives on the thermal stability and flame retardancy of intumescent Poly(lactic acid) system. Issue 6 (19th September 2018) - Xu, Lingfeng; Tan, Xinwen; Xu, Ruijie; Xie, Jiayi; Lei, Caihong
Abstract : Molybdenum disulfide (MoS2 ) with two‐dimensional (2D) lamellar structure was functionalized with melamine‐cyanuric acid (MCA) hybrids via a facile way. A core‐shell composite particle (MoMA) was obtained. Acting as one kind of synergistic flame retardant, it was mixed with traditional intumescent flame retardant (IFR) to prepare the flame retardant poly(lactic acid) composites by melt blending. UL‐94 V‐0 rating and LOI value of 29.8% for PLA composites were achieved while the total amount of flame retardants was 12 wt%, with the optimal weight ratio of IFR to MoMA 3:1. The inclusion of MoMA can enhance the amount of char residue and suppress the pyrolysis rate. The thermal degradation kinetic studies indicated that more pyrolysis conversion energy was needed. Finally, the investigation of char residue further confirmed that the addition of MoMA can improve the continuity and thermal stability of intumescent char layer and promote its graphitization degree. The condensed phase mechanism was mainly responsible for the improved flame retardant performance. This work suggests a novel strategy for improving flame retardant performance of PLA by combination of MoMA with IFR. The mechanical properties were studied as well. POLYM. COMPOS., 40:2244–2257, 2019. © 2018 Society of Plastics Engineers